Improvement of biofloc system for post larval rearing of giant freshwater prawn (Macrobrachium rosenbergii de Man, 1879) - Hosain, Md. Eilious (2021)
Giant freshwater prawn, Macrobrachium rosenbergii, is a commercially important crustacean, which is being cultured throughout the South-East Asia. The production of M. rosenbergii has been declined owing to lack of adequate post larvae (PL) production, non-effective farming system and diseases that cause high economic losses. Biofloc technology (BFT) can be an alternative culture system as it has been proven a viable culture system that improves water quality, provides live feeds and health care of culture species as well as increases the production of many fishes, prawns and shrimps. Little report is published on prawn productive performance in biofloc technology system (BFT) so far. This study was conducted to investigate the growth, survival and proximate composition of M. rosenbergii PL in BFT. Therefore, five experiments were conducted on nursery phase of M. rosenbergii PL to identify the suitable carbon source, C-N ratio, salinity and floc volume, and influence of copepod addition in BFT under completely randomized design of each treatment with triplicate. The first experiment tested five carbon sources i.e., wheat bran, rice flour, maize starch, molasses and palm kernel cake for biofloc. The PL growth was similar (P > 0.05) among five carbon sources. PLs survival (88.66%) was higher (P < 0.05) in maize starch and followed by rice flour (73.0%), molasses (68.33%), wheat bran (61.0%) and palm kernel cake (56.33%) treatments. The better FCR (2.21) and the highest lipid content (1.98% dry weight) were obtained in maize starch bioflocs than other four carbon sources. The water quality parameters viz. temperature, pH, dissolved oxygen and ammonia did not differ (P > 0.05) among five different carbon treatments. The second experiment examined the effects of four C-N ratios of 10, 15, 20, 25 and clear water system as control. Specific growth rate (SGR) was similar between the control (9.29% d-1) and the CN-20 (9.47% d-1) and CN- 25 (9.34% d-1) treatments which were significantly higher than that in the C-N10 treatment (8.03% d-1). A higher survival (87.34%) was obtained in the C-N ratio 20 when compared to control (80.33%) and other C-N ratios groups, but no significant differences among five treatments were observed. The best FCR (2.65) was observed in the C-N ratio 20 treatment. Biofloc crude protein content was higher in the C-N ratio 20 than CN ratio 10, 15 and 25 groups. The third experiment was conducted to compare the performance of BFT under four different salinities (0, 5, 10 and 15‰). Better growth of PLs were found in 10‰ and 15‰ saline water biofloc system. A higher survival (85.66%) of M. rosenbergii PL was obtained in 15‰ biofloc system and followed by10‰, 5‰ and freshwater BFT. The best FCR was found in 15‰ and 10‰ salinity groups. Ciliate and rotifer abundances were higher in 15 ‰ saline water biofloc system than 10‰, 5‰ and freshwater biofloc system. A lower density of Vibrio spp. remained in 15‰ biofloc system than in 10‰ system. The fourth experiment investigated the effects of different floc volume of 2-5, 7-10 and 12-15 ml L-1 as well as zero-exchange BFT (control). A higher (P < 0.05) prawn survival (82.33%) was obtained in 2-5 ml L-1 floc treatment and followed by 7-10, 12-15 ml L-1 and zero-exchange BFT treatments. Vibrio spp. density was lower (P < 0.05) in 2-5 ml L-1 floc treatment than 12-15 ml L-1 and zero-exchange BFT. The fifth experiment was conducted to evaluate the effects of copepod addition in BFT under three treatments i.e., clear water system as control, BFT with or without copepods addition. A higher final weight (117.23 mg), weight gain (107.82 mg), SGR (8.40 % d-1), and survival (94.46%) of PLs were found in BFT with copepod addition treatment (P < 0.05) than BFT without copepod and control. The best FCR (1.08) and crude protein content (66.91%) in PLs were significantly higher (P < 0.05) in the copepod addition BFT than without copepod addition BFT and control. Significantly lower ammonia was found in two BFT groups than control. Overall, the study suggested that maize starch as carbon source; C-N ratio of 20, salinity range of 10- 15 ‰, floc volume 2-5 ml L-1 and addition of copepod for the better growth and survival of M. rosenbergii PL in the nursery phase using BFT. Thus, the biofloc based nursery system could be implemented in commercial venture of M. rosenbergii industry to enhance the productivity and profit.